1973
DOI: 10.1111/j.1365-2222.1973.tb01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgE levels and the use of sodium cromoglycate (BP) in hay fever: a study of forty‐six patients from a single general practice

Abstract: Summary In a double blind trial of nasal spray of sodium cromoglycate (DSCG) for hay fever, fifteen of twenty‐three patients taking the drug were helped, compared with thirteen of twenty‐three receiving placebo—a statistically insignificant difference. Serum levels of IgE were raised in thirty‐eight of forty‐four patients examined. There was no significant difference between preseasonal and seasonal serum IgE levels in either of the DSCG or the placebo group. Serum IgE levels were significantly higher in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1973
1973
1984
1984

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Abnormally high serum IgE levels together with eosinophilia acquired on gold therapy and remitting on gold withdrawal is suggestive of a type I hypersensitivity reaction. Type I reactionare well recognized in various allergic states and the c,rabination of raised IgE and eosinophilia has been reported in tropical filariasis and hay fever (Manners and Ezeoke, 1973). Type I hypersensitivity reactions due to drugs are uncommon, though occasionally seen with penicillin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormally high serum IgE levels together with eosinophilia acquired on gold therapy and remitting on gold withdrawal is suggestive of a type I hypersensitivity reaction. Type I reactionare well recognized in various allergic states and the c,rabination of raised IgE and eosinophilia has been reported in tropical filariasis and hay fever (Manners and Ezeoke, 1973). Type I hypersensitivity reactions due to drugs are uncommon, though occasionally seen with penicillin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Capel & McKelvie (1971) reported that, on inhalation of sodium cromoglycate powder, 41% of adults improved, and Morrison Smith (1971) that 50% of children improved. Blair & Herbert (1973) and Manners & Ezeoke (1973) found 65% of their patients improved on an aqueous solution of sodium cromoglycate. Bagratuni (1960) observed that 70% improved on promethazine hydrochloride, 92% on phenindamine tartrate, 55% with prednisolone spray, and 50% with hydrocortisone snuff.…”
Section: Discussionmentioning
confidence: 99%
“…In 1972 there was some doubt as to the efficacy of S.C.G. solution in hay fever (Manners, 1973) but this may have been due to inadequate and irregular antigenic challenge. From the results described in the present paper, it is concluded that during periods of high grass pollen counts in Great Britain, S.C.G., used either as a spray or as a powder, is an acceptable means of treating hay fever.…”
Section: Discussionmentioning
confidence: 99%